Tashmim Al-Mawad At-Ta'limiyyah Li Maharah Al-Qira'ah Li Ath-Thalibat Qism Tiknulujiya Al-Ma'lumat - Mabruroh Mabruroh; Aulia Gustiana (Institut Agama Islam Negeri (IAIN) Metro, 2020)
The University of Darussalam Gontor is the leading university in spreading and teaching the Arabic language in Indonesia. So this university requires all its students to learn and master the Arabic language, and it is not limited to students of Arab and Islamic studies only, but also includes all students in disciplines other than Arabic and Islamic. Among these specializations is the information technology specialization. In this specialization, students are required to be familiar with the Arabic language and mastery of it. Still, nevertheless, they did not have a book on teaching the Arabic language related to the topics of information technology, which makes the position of education somewhat ineffective. Based on this and to implement the university's mission, the researcher tries to design educational materials for the skill of reading for students of the Department of Information Technology at the University of Dar es Salaam Contour. The research methodology is a research and development methodology. And the method of collecting data through the questionnaire and the test questions. From the research results, this educational material in the form of an educational book is valid and useful for the education process.